Εμβύθιση στα ψηφιακά παιχνίδια: μία μελέτη περίπτωσης των στοιχείων ενός παιχνιδιού που αναδίδουν καθηλωτικές εμπειρίες - Κατσακιώρης, Δημήτριος (2025)
This thesis focuses on the study of immersion in video games. Before delving into the specifics, it is essential to establish a clear understanding of the relevant terminology. Immersion as a concept, is not limited to game design alone. Instead, it serves as a broader concept that encompasses a range of experiences where an individual becomes fully engaged and absorbed in an activity or environment. This absorption can occur while reading a book, watching a movie, playing a sport, or even participating in a conversation. It is connected to concepts such as flow (absorption in a challenging activity which strikes a balance between the player’s skill level and the level of difficulty presented by the game), presence (the sensation of being physically and psychologically present within the virtual or simulated environment of a game) and narrative/imaginary immersion (the ability of a game to evoke and sustain a sense of emotional connection in players, allowing them to mentally and emotionally invest themselves in the game world, its characters, narratives, and overall experience). Despite the widespread use of the term “immersion” by game designers, players and journalists, there is no universally accepted, definitive definition of immersion within the field of game studies or other associated disciplines. Numerous papers present varying viewpoints on what constitutes an immersive experience. To address this gap, my thesis aims to explore how immersion is described in game design and how it is viewed within different game design frameworks. By understanding the constituents of a game that facilitate immersive experiences, I seek to measure and evaluate their significance through a case study. My hypothesis posits that different components of a game have varying degrees of impact on immersion, indicating that some elements are more influential than others. To test this hypothesis I created a demo of a game and conducted an experiment to test which of its components had the greatest impact on immersion, by enabling and disabling specific ones. As for the structure of my thesis, firstly I’ll analyze the aforementioned terminology and explain the relations and interactions between the concepts. After that, I am going to describe how different game design frameworks view immersion, which Is important as it describes how designers view games as holistic systems. Then I will explain the conceptual design, meaning the mental process behind the creation of both the demo and the experiment along with what I wanted each version of the demo to achieve. Then I will describe the implementation of said goals, the process of prototyping the demo, and the design of the questionnaire I used to measure immersion. Finally I will be analyzing the results, run significance tests and comment on my findings.